Evaluation of Pyrethrin Formulations on Dengue/Dengue Haemorrhagic Fever Vectors in the Laboratory and Sublethal Effects - S Sulaiman; K Fadhlina; O Hidayatulfathi (Tehran University of Medical Sciences, 2007)
In Southeast Asia, Aedes aegypti (L.) has been incriminated as principal vector of dengue viruses and Ae. albopictus as the secondary vector of dengue fever. Therefore, the aim of this study was to investigate the effectiveness of three for-mula¬tions of pyrethrin derived from Tanacetum cinerariaefolium against the dengue/dengue haemorrhagic fever vectors Aedes aegypti and Ae. albopictus in the laboratory. The testings employed 2 methodologies: the WHO Larval Bioassay and WHO Adult Bioassay. The results showed that all the three pyrethrin formulations had larvicidal and adulticidal activi-ties. The impact of the sublethal doses of pyrethrin formulations on Aedes spp. larvae resulted in 4-6% of alive adult emergence compared to 90% of Ae. aegypti emerging adults and 96% Ae. albopictus alive adult emergence in the control. The impact of sublethal doses of the pyrethrin formulations caused very low fecundity on both Aedes spp. compared to the control (P< 0.05).